Efektivitas Kegiatan Uji Emisi Kendaraan Kegiatan Bermotor di Dinas Perhubungan Kota Surabaya dalam Mencegah Pencemaran Udara - Rais, Farhan Fauzan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Effectiveness refers to the implementation of policies that are structured and can achieve the desired goals. The policy in question covers both the central government and regional governments. In the regional government sector, regional leaders often make their own policies in their government, especially policies to prevent public air pollution. The Surabaya City Government implements policies to prevent air pollution. The air pollution prevention policy is addressed to the Surabaya City Transportation Department. In this case, the Surabaya City Transportation Service is tasked with routinely testing motor vehicle exhaust emissions. This is because motor vehicle exhaust gas is one of the main causes of air pollution. By considering the dangers of motor vehicle exhaust emissions on clean air quality, two emission test methods have been implemented in an effort to prevent air pollution. These two methods are believed to be able to prevent air pollution if carried out in accordance with applicable regulations. This is considered quite effective because many motorized vehicles are required to comply because if they don't, heavy sanctions will be imposed. The main aim of implementing this policy is to maintain air quality in the city of Surabaya, which is a densely populated metropolitan city. This research applies an observational approach, with a field survey of the Transportation Service's emission testing activities in the Supervision and Control Sector.